2013
DOI: 10.2174/18722083113079990003
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy and Anodic Porous Allumina of Nucleic Acid Programmable Protein Arrays

Abstract: The methodological aspects are here presented for the NAPPA (Nucleic Acid Programmable Protein Arrays) characterization by atomic force microscopy and anodic porous alumina. Anodic Porous Alumina represents also an advanced on chip laboratory for gene expression contained in an engineered plasmid vector. The results obtained with CdK2, CDKN1A, p53 and Jun test genes expressed on NAPPA and the future developments are discussed in terms of our pertinent and recent Patents and of their possibility to overcome som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Lectin-coated QDs (Poly)saccharide Protein glycosylation FRET between QDs-AuNPs [53] GNP (Poly)saccharide Lectin Fluorescence of FSNPs [54] NiNTA-DsRed FT Proteins Immobilization concept Fluorescence [55] Cys-DNA + recombinant fusion proteins Proteins Immobilization concept Fluorescence [56] DDI oligonucleotide-tagged proteins Proteins EGF Location of subcellular area of cells [57] Lipidic membrane + ganglioside receptors Proteins Cholera toxin b SPRi [72] SWNT + RA-specific (CCC) peptide Peptides Rheumatoid factor QCM [73] A-enolase peptides Peptides Sera-specific PDAC Abs QCM_D [74] Aptamer-AgNPs Nucleic acids/aptamers PDGF-BB SPR/fluorescence of modified AgNPs [58] ssDNA aptamer monolayer Nucleic acids/aptamers Thrombin Nanoparticles-enhanced SPRi [59] DNA bar code Nucleic acids/aptamers PSA NPs absorbance [75] DNA template Nucleic acids/aptamers BRIP1, Jun, ATF2 QCM_F + QCM_D [76] DNA template on anodic porous alumina Nucleic acids/aptamers CdK2, CDKN1A, p53, Jun AFM [77] Fluorescent SWNT + His-tagged proteins…”
Section: Recognition Probementioning
confidence: 99%
See 1 more Smart Citation
“…Lectin-coated QDs (Poly)saccharide Protein glycosylation FRET between QDs-AuNPs [53] GNP (Poly)saccharide Lectin Fluorescence of FSNPs [54] NiNTA-DsRed FT Proteins Immobilization concept Fluorescence [55] Cys-DNA + recombinant fusion proteins Proteins Immobilization concept Fluorescence [56] DDI oligonucleotide-tagged proteins Proteins EGF Location of subcellular area of cells [57] Lipidic membrane + ganglioside receptors Proteins Cholera toxin b SPRi [72] SWNT + RA-specific (CCC) peptide Peptides Rheumatoid factor QCM [73] A-enolase peptides Peptides Sera-specific PDAC Abs QCM_D [74] Aptamer-AgNPs Nucleic acids/aptamers PDGF-BB SPR/fluorescence of modified AgNPs [58] ssDNA aptamer monolayer Nucleic acids/aptamers Thrombin Nanoparticles-enhanced SPRi [59] DNA bar code Nucleic acids/aptamers PSA NPs absorbance [75] DNA template Nucleic acids/aptamers BRIP1, Jun, ATF2 QCM_F + QCM_D [76] DNA template on anodic porous alumina Nucleic acids/aptamers CdK2, CDKN1A, p53, Jun AFM [77] Fluorescent SWNT + His-tagged proteins…”
Section: Recognition Probementioning
confidence: 99%
“…AFM is applicable to a wide range of molecular species, many of which are difficult to label by popular tags, including proteins and other molecules [108]. AFM can validate protein expression on the array surface, whereas these measurements were applied to demonstrate gene expression using mica-coated slides containing 16 spots, having printed one 300 microns NAPPA spot containing around 400 genes [77]. Moreover, AFM-based scratching techniques offer unique approach for the fabrication of nanoscaled arrays [109], which can serve as a platform for implementation of other nanotechnological recognition probes, as aptamers or s ynthetic peptides.…”
Section: Atomic Force Microscopymentioning
confidence: 99%
“…On excitation by a mercury lamp at ~530 nm wavelength, fluorescence emission was observed at ~593 nm in real time by a sensitive CCD photo camera coupled with the optical microscope. From the fluorescence maps frequency histograms were obtained, before and after a rinsing treatment that showed possible reuse of the substrates, for potential application in biomedical assays [21]. In particular, the authors observed by AFM the occurrence of APA pores in excess of 1 µm, even if anodization was carried out under standard conditions (0.5 M oxalic acid, 5-20 °C, 50 V).…”
Section: Volume 1 | Issuementioning
confidence: 99%
“…In recent years, APA has attracted significant interest for sensor [1][2], photonic devices [3] and protein crystals growth [4,5] due to the specific characteristics of its ordered multi-cavities array [6]. The fast development of the proteomic field and the complexity proteinprotein and proteins-small molecules interaction require new advanced protein arrays in micro and nanoscale dimension.…”
Section: Introductionmentioning
confidence: 99%